Moon Girl and Devil Dinosaur. BFF. #2, Old dogs and new tricks - Montclare, Brandon; Hadley, Amy Reeder, 1980- (Abdo Spotlight, 2018)
Lunella Lafayette is a preteen living in New York who happens to be a super-genius with an inhuman gene and an alter-ego known as Moon Girl. She hopes to use her intelligence to change the world. Alongside Devil Dinosaur, a red-scaled, prehistoric beast that slipped through a space-time portal from the past, Moon Girl must fight off the Killer Folk who are now in New York.